PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK TALK WRITE (TTW) UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS III SDN 112 PEKANBARU - Panggabean, Widy Rahmadhani; Marhadi, Hendri; Witri, Gustimal (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract. Based on the observation and documentation writers do, that the class III student learning outcomes SDN 112 Pekanbaru lower than that encountered symptoms in the subject, which is of 40 students, only 22 (55.00%) were completely or scored above KKM 70. the remaining 18 (45.00%) have not been completed, with the average value grade of 68.23. This research was conducted in SDN 112 Pekanbaru are in class III, while the timing of the study was conducted in the first semester of Academic Year 2016-2017. Design of this research is the Classroom Action Research (PTK). As the subjects in this study were teachers and students of class III SDN 112 Pekanbaru, with the number of 40 students, consisting of 23 men and 17 women. Based on the results of research and pembahsan it can be concluded that the application of the learning model Think Talk Write (TTW) can improve student learning outcomes SDN 112 class III Pekanbaru. The study concluded that the application of the learning model Think Talk Write (TTW) can increase the activity of teachers and students. Application of learning model Think Talk Write (TTW) can improve student learning outcomes visible from basic score with an average of 68.23 increased in the first cycle to 72.00 ie by the thoroughness of 29 students or 73.00% and the second cycle increased to 76.75 or completeness 90.00% with an increase of 21:46%.Key Words: Think Talk Write (TTW), learning outcomes.